A controlled trial of the impact of exposure to positive images of dentistry on anticipatory dental fear in children - Jeong S-H, Chung J-K, Choi Y-H, Sohn W, Song K-B (Blackwell Synergy, 2006)
The purposes of this study were to investigate the level and distribution of job satisfaction and to explore work environment factors associated with job satisfaction of South Korean dentists.